Visible light-emitting diode light-driven one-pot four component synthesis of poly-functionalized imidazoles under catalyst- and solvent-free conditions. (24th July 2020) - Patel, Geetika; Patel, Ashok Raj; Banerjee, Subhash
Abstract : A visible light-emitting diode light-driven green and sustainable protocol has been demonstrated for the one-pot four component synthesis of poly-functionalized imidazoles under catalyst- and solvent-free conditions. Abstract : Here, we have demonstrated the visible LED light-promoted synthesis of poly functionalized imidazole derivatives by a four component condensation of 1, 2-diphenyl 1, 2-diketone aromatic aldehydes and ammonium acetate and/or amines in excellent yields. The solvent- and catalyst-free reaction conditions, excellent isolated yields of the products, shorter reaction times, and simple isolation and purification of the products make the present protocol efficient and a green alternative to existing protocols.